Ethnic relations in Macedonia in the early 20th century - Giza, Antoni (Balcanica Posnaniensia. Acta et studia, 2001)
The article analyzes the ethnic structure of the Macedonian lands during the first decade of the twentieth century and the political and territorial disputes associated with it. The starting point is the exceptionally complex ethnic composition of Macedonia, which remained under Ottoman rule and was the object of rivalry among neighboring states. The aim of the study is to present the ethnic composition of the region and explain the causes of disputes concerning the identity of its inhabitants and the territorial affiliation of Macedonia. The author employs a historical-political method, using statistical data, geographical studies, and sources concerning the policies of Balkan states. The article also discusses changes in the region’s ethnic boundaries and the influence of neighboring states’ national policies on the formation of national consciousness among the population. It is demonstrated that Macedonia’s ethnic structure was inseparably linked to religious divisions, which further complicated the political situation. The conclusions lead to the observation that Macedonia was one of the most ethnically complex regions of the Balkans and that competition over its historical and national heritage became one of the principal sources of tension in the region during the twentieth century.